Principles and Steps for Developing Human Resources in the LPQ Darul Muta'allimin Semarang - Rahmasari, Zulfa; Subiyantoro, Subiyantoro (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
Human resource development is an essential thing to do as a long-term investment for an organization, including educational institutions. Much research has been carried out to determine the influence of human resource development, but only focuses on the large/small level of influence without explaining how concrete steps for human resource development are carried out. This research aims to determine 1) Principles of human resource development at the LPQ Darul Muta'allimin Semarang, 2) Steps for developing human resources at the LPQ Darul Muta'allimin Qur'an Semarang. This type of research is qualitative research with descriptive methods. Data collection techniques used observation, interviews with the head and teachers also staff of LPQ Darul Muta'allimin, as well as documentation. Data analysis techniques use data reduction, data presentation and drawing conclusions. The results of this research show that 1) The principles applied by LPQ Darul Muta'allimin in implementing human resource development programs, namely istiqomah, are carried out routinely and continuously, customized according to the needs and goals to be achieved by LPQ, active participation of all LPQ stakeholders Darul Muta'allimin, as well as evaluation. 2) Steps for developing human resources for LPQ Darul Muta'allimin teachers, namely examining needs, creating instructional concepts, determining participants, implementing training, and evaluating follow-up of the human resource development program.